PENGETAHUAN JURNALISTIK PEGAWAI HUMAS PEMERINTAH DALAM KEGIATAN PUBLISITAS - Rahmita Saleh; Muhammad Iqbal Sultan; Muhammad Farid (KAREBA : Jurnal Ilmu Komunikasi, 2015)
Abstract Public relations require skills in journalistic to generating quality publicity. This researh aims to describe and analyze the knowledge of journalism public relations employee of South Sulawesi Provincial Government in the publicity activities. This study used a qualitative descriptive approach using the techniques of data collection through in-depth interviews and observations of public relations personnel assigned to conduct publicity activities. Analysis using an interactive model of Huberman and Miles were taken through the stages of data reduction, data display, making conclusions and verification. The results showed that public relations employee of South Sulawesi Provincial Government conduct publicity activities through three stages, namely the coverage of the government's agenda, write and distribute press releases to journalists. Writing a press release is not adjusted to the rules of journalistic writing and the medium. Are loaded in the media have gone through editing stages agenda tailored to each medium, so that the core of the publicity that was sent was not published. This research concluded that government public relations employee of South Sulawesi Provincial Government, in generating publicity decent fit in the mass media, still lack of mastery in terms of expertise and knowledge in the field of journalism.Abstrak Humas memerlukan kemampuan di bidang jurnalistik agar dapat menghasilkan publisitas yang berkualitas. Penelitian ini bertujuan untuk menggambarkan dan menganalisis pengetahuan jurnalistik pegawai humas Pemerintah Provinsi Sulawesi Selatan dalam menjalankan kegiatan publisitas. Dalam penelitian ini digunakan pendekatan deskriptif kualitatif dengan menggunakan teknik pengumpulan data melalui wawancara mendalam dan observasi terhadap pegawai humas yang bertugas melakukan kegiatan publisitas. Teknik analisis data menggunakan model interaktif Huberman dan Miles yang ditempuh melalui tahap reduksi data, display data, pengambilan kesimpulan dan verifikasi. Hasil penelitian menunjukkan bahwa pegawai humas Pemerintah Provinsi Sulawesi Selatan melakukan kegiatan publisitas melalui tiga tahap, yaitu peliputan agenda pemerintah, menulis press release dan menyebarluaskan kepada wartawan. Penulisan press release tidak disesuaikan dengan kaidah penulisan jurnalistik dan mediumnya. Pemuatannya di media massa telah melalui tahap pengeditan disesuaikan dengan agenda masing- masing media, sehingga inti dari publisitas yang dikirim tidak terpublikasi. Penelitian ini menyimpulkan bahwa pegawai humas Pemerintah Provinsi Sulawesi Selatan, dalam menghasilkan publisitas yang layak di muat di media massa, masih kurang memiliki penguasaan dalam hal keahlian dan pengetahuan di bidang jurnalistik.